Parque Tecno - Sostenible de educación superior Usme - Guerrero Méndez, Cristian David (Universidad Antonio Nariño, 2021)
In the present work, the investigation is carried out on the panorama of higher education in the city of Bogotá, and it focuses mainly on the accessibility and coverage of the peripheral sectors of the south; that they share some conditions or similarities (spatial, socioeconomic, among others), thus exposing the difficulties of the inhabitants to give continuity to their post-secondary training process; Due to the configuration and location of the higher education facilities that both public and private that are concentrated in the central-north area, bases for the development of the next project that is exposed, which formulates the techno-sustainable park in the town of Usme As a solution for this need, a proposal articulated to the requirements of the Territorial Organization Plan (POT) where this Town of Usme is defined as a strategic place within its Master Plan of Educational Facilities for the construction of higher education educational facilities.